Awareness of adverse effects of lead-containing cosmetics among the adolescence and young adult population in Chennai. A survey (Medico Legal Update, 2021)
Background: Lead and it’s compound induced health problems are continue to be an important, preventablepublic health issue. The common source of lead exposure in modern days is cosmetic products.Aim and Objectives: The study aims to evaluate the awareness about the adverse effects of lead-containingcosmetics in adolescence and the young adult population including factors influencing customers, knowledgeabout the product ingredients, and quality.Materials and Method: In this study, a questionnaire was prepared using Google form and circulatedamong the adolescence and young adult subjects to assess the awareness about the adverse effect of lead incosmetics. The study sample comprised of totally 203 participants of both males and females with the agegroup between 16 to 24 years.Results: In this study, it is found that 87% of the participants were aware that cosmetic products harm theirhealth. 78% of the participants know lead and its compounds present in the cosmetics. 86% of participantshave the habit of checking the ingredients and quality of cosmetic products. About 96% of the participantswere influenced by the advertisement of the product before buying it.